Toxic behaviors from the perspective of teenagers: politics and "activism" on social media (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper investigates elements of the internet considered harmful by young people, with an emphasis on attitudes and content related to politics. To this end, the results of a content analysis of semi-structured interviews with high school students from public schools in Aracaju-SE and Maceió-AL are presented. A significant number of teenagers mentioned issues related to political engagement on social media negatively, especially what they defined as "toxic militancy". This study contributes to the reflection on the political engagement of adolescents and proposes guidelines for an education oriented towards the safe and citizen use of networks.
Keywords: Social Media; Teenagers; Toxic Behavior; Politics Activism; Media Literacy